2015
DOI: 10.1021/cs501650j
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Effects on the Water Oxidation Activity of Co3O4/Porous Silica Nanocomposites

Abstract: We investigate the effect of microstructuring on the water oxidation (oxygen evolution) activity of two types of Co 3 O 4 /porous silica composites: Co 3 O 4 /porous SiO 2 core/shell nanoparticles with varying shell thicknesses and surface areas, and Co 3 O 4 /mesoporous silica nanocomposites with various surface functionalities. Catalytic tests in the presence of Ru(bpy )3 2+ as a photosensitizer and S 2 O 8 2-as a sacrificial electron acceptor show that porous silica shells of up to -20 nm in thickness lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 79 publications
0
36
0
Order By: Relevance
“…Studies on the effect of size of Co 3 O 4 on oxygen evolution showed that reducing the particle size with increasing the surface area improves the catalytic activity [37,38]. Nanocomposites of Co 3 O 4 with graphene, N-doped carbon hybrids, CNT and porous silica, etc., are shown to enhance the water oxidation catalytic activities by increasing the conductivity and surface area of the catalyst [39][40][41][42]. Co 3 O 4 also a plays an important role in photoelectrochemical water splitting.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the effect of size of Co 3 O 4 on oxygen evolution showed that reducing the particle size with increasing the surface area improves the catalytic activity [37,38]. Nanocomposites of Co 3 O 4 with graphene, N-doped carbon hybrids, CNT and porous silica, etc., are shown to enhance the water oxidation catalytic activities by increasing the conductivity and surface area of the catalyst [39][40][41][42]. Co 3 O 4 also a plays an important role in photoelectrochemical water splitting.…”
Section: Introductionmentioning
confidence: 99%
“…al with some modifications. 21 Firstly, cobalt nitrate hexahydrate (8.60 g) was dissolved in 100 ml of ethanol and the resulting mixture was stirred vigorously. Then, the mixture was heated up to 50 °C and kept for 30 min.…”
Section: Preparation Of Co 3 O 4 Nanoparticlesmentioning
confidence: 99%
“…al. 21 Briefly, CTAB (2.2 g) was added to a solution of 0.5 g of Co 3 O 4 nanoparticles in EtOH (350 mL), and then concentrated ammonia aqueous solution (40 mL, 28 wt %) was added dropwise to the reaction mixture under sonication. After the treatment for 20 min which followed by the addition of tetraethylorthosilicate (TEOS) (0.4 mL in 10 mL of EtOH) to the mixture under ultrasound irradiation, then solution was stirred for 20 h at room temperature.…”
Section: Preparation Of Co 3 O 4 @Sio 2 Nanoparticlesmentioning
confidence: 99%
“…Co 3 O 4 nanoparticles were prepared according to the previously reported procedure by Vela et al with some modifications (28). First, cobalt nitrate hexahydrate (8.60 g) was dissolved in 100 mL of ethanol and the mixture was vigorously stirred.…”
Section: Preparation Of Co 3 O 4 Nanoparticlesmentioning
confidence: 99%
“…The Co 3 O 4 @SiO 2 nanocomposites were prepared according to the previously reported method by Vela et al with some minor modifications (28). Briefly, CTAB (2.2 g) was added to a solution of Co 3 O 4 nanocomposites (0.5 g) in EtOH (350 mL), and then concentrated ammonia aqueous solution (40 mL, 28 wt %) was added dropwise to the reaction mixture for 20 min under sonication.…”
Section: Preparation Of Co 3 O 4 @Sio 2 Nanocomposites Under Ultrasoumentioning
confidence: 99%